Valuation of environmental goods and services: The case of Bale Mountains National Park, Ethiopia - Yilma Haroyu; Muktar Bayeh; Habte Wolle (African Journal of Environmental Economics and Management, 2016)
Valuation of non marketed environmental goods and services is newly emerging research area particularly in Ethiopia and other developing countries. The study was aimed to investigate willingness to pay for conservation of environmental services and local tourists' entrance fee of Bale mountains National Park as well as determinant factors affecting visiting interest of local community. The widely used and flexible technique of environmental valuation called contingent valuation method/CVM/ was used. Respondents were given hypothetical project of conserving the park. Hypothetical questions were prepared to elicit the maximum willingness to pay and Willingness to accept to conserve the park. Dinsho, Goba and Robe towns were purposefully selected from which 380 respondents were selected from stratified population using lottery method. Logistic regression model was used to quantitatively analyze socio-economic factors of local people to visit the park. The research finding indicated that visitors mean entrance fee WTP is over 3 times the current entrance fee. Maximum amount of willingness to pay for the proposed conservation project scenario varied from 0 to 1000birr (50$), whereas mean and mode were 35 $ and 10$. Regression analysis showed sex, age, family size, and education level were significant determinants of visiting the park. In addition, district/nearness, education level, job, awareness of biodiversity importance and status, and income level of respondents positively affected an individual’s willingness to pay. Generally, the survey was successful in eliciting willingness-to-pay for protecting the park and can potentially help policy makers as well as park managers to increase number of local tourists so as to increase revenue for conservation work.